Linear Algebra

posted by Who would know

which of the following functions is the inverse of F(X)=3x
F(X)=X (cubed)****
F(X)= X/3
This function does not have an inverse.
Thank you!

  1. bobpursley

  2. Bosnian

    Replace F(x)with y
    y = 3 x

    Interchange the variables

    x = 3 y Divide both sides by 3

    x / 3 = y

    y = x / 3

    Replace y with F(x)

    F(x)= x / 3

Respond to this Question

First Name

Your Answer

Similar Questions

  1. graph!

    how can the graph of f(x)= X^2-4X be used to obtain the graph of y=g(x) ?
  2. Math - Inverse Functions

    Find the inverses of the following functions. y = 3(x - 1)^2, x >= 1 Work: x = 3(y - 1)^2 x = 3(y - 1)(y - 1) x = 3(y^2 - y - y + 1) x = 3y^2 - 6y + 3 And now what do I do!?
  3. algebra

    1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). Use finite differences to determine the equation of the function. (b) Draw the graph of the function. (c) Draw the inverse on the graph. (d) Show at least two different …
  4. Calculus

    F(x) = 1-x and g(x) = 1/x These functions have the property that f = f^-1(inverse) and g = g ^-1. That is, the inverse of f is equal to itself and the inverse of g is also equal to itself. Take the composition of each function with …
  5. algebra

    Can someone help with inverse relations and functions?
  6. Calculus, check my answers, please! 3

    Did I get these practice questions right?
  7. Algebra

    what is the inverse of the linear parent function?
  8. Algebra

    Myra uses an inverse variation function to model the data for the ordered pairs below. (2, 30), (3, 20), (4, 15), (5, 12), (6, 10) Which statement best explains whether an inverse variation function is the best model for the data?
  9. Advanced Algebra

    What is the inverse of each of the functions defined by the following equations, if the inverse exists. If the inverse does not exist for the largest possible domain, limit the domain so that the inverse will exist. In each case, give …
  10. Advanced Functions 12

    A student writes, "The inverse of y = -√(x+2) is y = x^2 - 2." Why is this statement false?

More Similar Questions